2020
DOI: 10.1103/physreve.101.023311
|View full text |Cite
|
Sign up to set email alerts
|

Semi-Lagrangian lattice Boltzmann model for compressible flows on unstructured meshes

Abstract: Compressible lattice Boltzmann model on standard lattices [M. H. Saadat, F. Bösch, and I. V. Karlin, Phys. Rev. E 99, 013306 (2019).] is extended to deal with complex flows on unstructured grid. Semi-Lagrangian propagation [A. Krämer et al., Phys. Rev. E 95, 023305 (2017).] is performed on an unstructured second-order accurate finite-element mesh and a consistent wall boundary condition is implemented which makes it possible to simulate compressible flows over complex geometries. The model is validated through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 38 publications
1
21
0
Order By: Relevance
“…The results accurately matched the reference solution [58] with only minor oscillations visible, comparable to other recently introduced methods [60].…”
Section: Sod Shock Tubesupporting
confidence: 77%
See 1 more Smart Citation
“…The results accurately matched the reference solution [58] with only minor oscillations visible, comparable to other recently introduced methods [60].…”
Section: Sod Shock Tubesupporting
confidence: 77%
“…To measure the accuracy of the SLLBM for compressible flows, the smooth density propagation [59,60] was evaluated.…”
Section: B Smooth Density Propagationmentioning
confidence: 99%
“…As in [ 11 ], the lattice Boltzmann equations for the f - and g -populations are realized on the 3 27 discrete velocity set and where relaxation parameters and are related to the viscosity and thermal conductivity. The equilibrium f -populations in ( 3.6 ) are evaluated using the product-form, with and in ( 2.6 ), The last term in ( 3.6 ) is a correction needed to compensate for the insufficient isotropy of the 3 27 lattice in the compressible flow setting [ 11 , 13 15 ]: X is the vector with the components while the components of vectors are defined as 1 0 The equilibrium and the quasi-equilibrium g -populations, and in ( 3.7 ), are ...…”
Section: Lattice Boltzmann Model Of Mixture Momentum and Energymentioning
confidence: 99%
“…Another avenue are semi-Lagrangian methods [33][34][35][36][37], which start from a characteristic equation to resolve these issues. Promising results have been shown for wall-bounded turbulent flows [38] and even compressible flows [37,39,40].…”
Section: Introductionmentioning
confidence: 98%
“…In our previous works [39,40], it was demonstrated that by using an arbitrary Eulerian-Lagrangian (ALE) formulation in combination with a dual population LB formulation, highspeed compressible flows with moving geometries can be captured accurately and efficiently. However, in those works, only a single body was considered and the motion was prescribed.…”
Section: Introductionmentioning
confidence: 99%